The perceived public accountability among Malaysian public administrators: a validity test through confirmatory factor analysis / Aida Abdullah - Abdullah, Aida (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, Malaysia.., 2019)
Accountability is strongly emphasised in the public sector, recognised as a list of duties implemented in meeting needs and wants of the people. In this study, public accountability examined as roles of public employees divided into internal and external accountability persists to provide the exact representation of the actual role of employees in the public sector. The dichotomy provides an unprofound sense of what responsibilities are, especially within the Malaysian public sector. As such, this study was conducted among public administrators and items analysed through confirmatory factor analysis, and a final of 13 item-measurement construct validated. The findings show that internal and external accountability recognised as routine roles, which is placed under different ministries and efforts to strengthen public administrators' skills in the implementation of these tasks, can avoid any form of misconduct that could impair their work performance. The theoretical and methodological issues in relation to public accountability constructs are discussed in light of these findings.